2021
DOI: 10.1111/tpj.15306
|View full text |Cite
|
Sign up to set email alerts
|

Repeat proliferation and partial endoreplication jointly shape the patterns of genome size evolution in orchids

Abstract: Summary Although the evolutionary drivers of genome size change are known, the general patterns and mechanisms of plant genome size evolution are yet to be established. Here we aim to assess the relative importance of proliferation of repetitive DNA, chromosomal variation (including polyploidy), and the type of endoreplication for genome size evolution of the Pleurothallidinae, the most species‐rich orchid lineage. Phylogenetic relationships between 341 Pleurothallidinae representatives were refined using a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…The size of the endoreplicated part of the genome appears to have broader evolutionary implications, as its uniformity among evolutionary lineages (Figure 3 and Table 1), except in recent polyploids, suggests some constraint on this trait, and the evolution of genome size is restricted to the non-endoreplicated part. This is consistent with the findings of Chumová et al (2021), who showed different rates of evolution for the endoreplicated and non-endoreplicated parts of genome in orchids from the subtribe Pleurothallidinae.…”
Section: Taxonomic Implications Of Endoreplicationsupporting
confidence: 92%
See 2 more Smart Citations
“…The size of the endoreplicated part of the genome appears to have broader evolutionary implications, as its uniformity among evolutionary lineages (Figure 3 and Table 1), except in recent polyploids, suggests some constraint on this trait, and the evolution of genome size is restricted to the non-endoreplicated part. This is consistent with the findings of Chumová et al (2021), who showed different rates of evolution for the endoreplicated and non-endoreplicated parts of genome in orchids from the subtribe Pleurothallidinae.…”
Section: Taxonomic Implications Of Endoreplicationsupporting
confidence: 92%
“…This study originally builds on our long-term research on orchids, specifically the causes and consequences of the unique trait of partial endoreplication (Trávníček et al, 2015(Trávníček et al, , 2019Hřibová et al, 2016;Chumová et al, 2021). By investigating the pattern of endoreplication in many orchid genera, we found that the smallest amount of the endoreplicated part of the genome in all orchids hitherto studied is observed in the N. lactea group (∼12-13%).…”
Section: A New Path In Comprehensive Orchid Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the gametes are haploid also suggests the presence of molecular mechanisms that enable the isolation of the holoploid genome. This type of endoreplication, which appears to be specific to the Orchidaceae lineage in plants, has been successively termed “progressively PE” ( Bory et al., 2008 ; Trávníček et al., 2015 ; Hřibová et al., 2016 ), strict PE ( Brown et al., 2017 ), and more recently, PE ( Chumová et al., 2021 ; Trávníček et al, 2019) . To be in line with the latest works and to harmonize the terminology for this phenomenon, the term PE will be used in this work.…”
Section: Introductionmentioning
confidence: 99%
“…It is very high in Vanilla pompona (F = 81%) but rather low in Vanilla mexicana (F = 17%) ( Brown et al., 2017 ). Several studies on orchids have also shown that species prone to PE have a larger genome than those prone to conventional endoreplication ( Trávníček et al., 2015 , 2019 ; Chumová et al., 2021 ). Nevertheless, the molecular mechanisms involved in PE are not yet elucidated.…”
Section: Introductionmentioning
confidence: 99%